The structure, form and language of international environmental norms - from absolute to relative normativity - Niko Soininen (Edward Elgar Publishing, 2016)
International environmental law has a dual nature being both formal (attached to explicit state will) and instrumental (detached from explicit state will). In this chapter it is argued that normativity of international environmental legal norms is relativised due to the softening of hard law and hardening of soft law. The softening of hard law is caused primarily by the interpretative nature of language and the interplay between formalism and instrumentalism as interpretative paradigms. As a consequence, the normative content of hard law is always a matter of interpretation which by default causes hard law to be more or less indeterminate. The hardening of soft law is visible inter alia in the informal legal status that several soft law instruments such as UN resolutions, accords, executive board decisions and informal initiatives may enjoy through their legitimacy and effectiveness. This results in some soft law instruments gaining relative legal effect even when lacking formal legal status. Based on these observations it is concluded that the normativity or validity of legal norms in international environmental law can only be evaluated after a careful analysis of all the traces of normativity (form, legitimacy and effectiveness) at play.